2016
DOI: 10.18494/sam.2016.1256
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Nitrite-Ion Sensor Based on Electrodeposited Sm-Based Perovskite-Type Oxide Thick-Film Electrode

Abstract: Perovskite-type oxide SmBO 3 (B = Cr, Mn, Fe, Co) powders were prepared by a polymer precursor method at 750 °С and systematically investigated for electrochemical sensing properties for NO 2 − . The SmBO 3 -modified carbon-felt electrodes could be prepared by an electrophoretic deposition (EPD) method without sintering. Among the oxide deposited electrodes, the SmFeO 3 modified electrode showed the highest sensitivity to NO 2 − with 11.9 mA M −1 cm −2 and a linear sensing range between 5.0 × 10 −5 and 1.0 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Both of them present e g orbital fillings that are critical in oxygen electrocatalysis Figure b,c illustrates the Fe 2p and Mn 2p core-level spectra of PBCMF-1, which could be deconvoluted into several characteristic subpeaks of Mn 2+ /​Mn 3+ /​Mn 4+ and Fe 3+ /​Fe 4+ . , The calculated average valences of Mn and Fe were 3.03 and 3.40, respectively, from which we can also calculate the 3−δ value in PBCMF-1. It is found that the calculated 3−δ value was in good agreement with the one obtained from the iodometric titration analysis (Table S5), which in turn proves that the e g occupancies obtained from the XPS survey are reliable.…”
Section: Resultsmentioning
confidence: 95%
“…Both of them present e g orbital fillings that are critical in oxygen electrocatalysis Figure b,c illustrates the Fe 2p and Mn 2p core-level spectra of PBCMF-1, which could be deconvoluted into several characteristic subpeaks of Mn 2+ /​Mn 3+ /​Mn 4+ and Fe 3+ /​Fe 4+ . , The calculated average valences of Mn and Fe were 3.03 and 3.40, respectively, from which we can also calculate the 3−δ value in PBCMF-1. It is found that the calculated 3−δ value was in good agreement with the one obtained from the iodometric titration analysis (Table S5), which in turn proves that the e g occupancies obtained from the XPS survey are reliable.…”
Section: Resultsmentioning
confidence: 95%